TÜRK İLİMLER AKADEMİSİ KURULMASI HAKKINDA DÜŞÜNCELER - AYHAN PALA (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
Turkish Academy of Sciences must be established as an international institution with an agreement between the Turkish-speaking countries. The Academy would search cultures of all Turkish-speaking states, autonomous states and regions. This institution would become the most important centre in academic cooperation of all these Turkish-speaking countries and would provide the cooperation between the above-mentioned institutions, universities and academies between Turkey and these countries. This Academy would realize common projects and would serve to study and develop the common culture of Turkish-speaking countries. Moreover, the practice of maintaining the coordinated works between these countries would also prevent the time and labour losses which is also possible by the works of this institution. One of the first duties of the Academy must be studying the Turkish archaeology. It must be taken into consideration that large part of the archaeological studies related to the Turkish history were carried by non-Turks, that there are still many works to be done and that there is a necessity to educate new masters in this field. Some other working spheres of the Academy must be on Turkish dialects and on preparing various dictionaries.